Tuning Reactivity in Pd‐catalysed C(sp3)‐H Arylations via Directing Group Modifications and Solvent Selection. Issue 22 (24th September 2020) - Coomber, Charlotte E.; Porter, Michael J.; Aliev, Abil E.; Smith, Peter D.; Sheppard, Tom D.
Abstract: The palladium‐catalysed sp 3 C−H arylation of a selection of saturated amine scaffolds was investigated using substituted picolinamide directing groups. On the bornylamine scaffold, highly selective monoarylation takes place using unsubstituted picolinamide or 3‐methylpicolinamide, whereas a double C−H arylation occurs with other substituents present, becoming a significant product with 3‐trifluoromethylpicolinamide. DFT calculations were used to help rationalise the effect of directing groups on the C−H palladation steps which were found experimentally to be irreversible. The substituted picolinamide directing groups were also examined on acyclic amine scaffolds and in many cases increased yields and selectivity could be obtained using methylpicolinamides. For a selection of other amine scaffolds, the yield of C−H arylation could be improved significantly using 3‐methylpicolinamide as the directing group and/or 3‐methylpentan‐3‐ol as the solvent Abstract :